Correlation of cells with proteins in extracellular polymeric substance matrix of bioaggregates. (February 2022) - Chen, Ming-Yuan; Lee, Yu-Jen
Abstract: The bioaggregates for wastewater treatment are made of cells and the extracellular polymeric substances (EPS) secreted by the cells. This study performed multiple fluorescence staining technique and confocal laser scanning microscope (CLSM) observations to probe the spatial distributions of cells, proteins, and α-polysaccharides in the activated sludge flocs and the aerobic granule. The pair correlation analysis revealed that the cells have high affinity to proteins instead of to polysaccharides. Based on the patterns of the pair correlation functions, the sludge floc was shown to be a matrix reinforced by α-polysaccharides with embedded microaggregates of cells and proteins of size of 2–3 cell diameters. Graphical abstract: Unlabelled Image Highlights: Distributions of DNA, proteins and α-polysaccharides in bioaggregates were probed. Pair correlation analysis on CLSM images was performed. Cells are for the first time confirmed to present with proteins but polysaccharide. Floc is polysaccharide-reinforced matrix with embedded cell-proteins aggregates.